Inhibition Activity of Ultrasonic-Assisted Extract of Sonneratia caseolaris Mangrove Leaves (UCESc) against Escherichia coli - Tanti Dwi Oktavia; Pramono, Heru; Yuli Pujiastuti, Dwi; Wina Sapphira, Eunike; Alvianita Az-Zahra, Naela (Universitas Islam Lamongan, 2025)
Mangrove Sonneratia caseolaris’s leaf contains bioactive compounds such as alkaloid, flavonoid, phenolic, and tannin. Previously, crude extract of S. caseolaris leaf was reported has potential as antibacterial. However, information on antibacterial activity profile of ultrasonic- assisted extract of S. caseolaris leaf against Escherichia coli was limited. Therefore, the aim of this study was to determine the effect of ultrasonic-assisted extraction on S. caseolaris leaf extract’s antibacterial activity against E. coli. The extraction was performed using ultrasonicator bath at 40 KHz, 40 °C for 25 minutes using 96% ethanol as a solvent. The phytochemical analysis was indicated that the crude extract Sonneratia caseolaris (UCESc) contains flavonoid, saponin, steroid, and tannin, but lack of alkaloid. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of UCESc were performed with microdilution with MIC of 24 mg/mL and MBC is 48 mg/mL. The antibacterial assay using disc dilution assay indicated that the best activity was at a concentration of 96 mg/mL with an inhibition zone of 4.88 mm. This study suggested that ultrasonic assisted extraction is potential approach to extract S. caseolaris bioactive compounds with a potential to be used as an antibacterial.